2020
DOI: 10.1002/bies.202000140
|View full text |Cite
|
Sign up to set email alerts
|

Tissue‐disruption‐induced cellular stochasticity and epigenetic drift: Common origins of aging and cancer?

Abstract: Age-related and cancer-related epigenomic modifications have been associated with enhanced cell-to-cell gene expression variability that characterizes increased cellular stochasticity. Since gene expression variability appears to be highly reduced byand epigenetic and phenotypic stability acquired through-direct or long-range cellular interactions during cell differentiation, we propose a common origin for aging and cancer in the failure to control cellular stochasticity by cell-cell interactions. Tissuedisrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 109 publications
(170 reference statements)
2
7
0
Order By: Relevance
“…Our view shares with the tissue organization field theory (TOFT) of cancer premise that cells are not quiescent by default, but rather maintain continuous internal drive, while homeostasis is enforced on them by the tissue level of organization ( Sonnenschein and Soto, 2020 ). It is also consistent with the idea that aging affects the propensity for cancer development through the decrease in effective tissue homeostasis ( Capp and Thomas, 2021 ). Our conceptual framework may open the door to novel directions in cancer research and therapeutic development as it shifts the focus from looking for additional molecular targets to treating the learning cancer ecosystem as a whole ( Weinberg, 2014 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our view shares with the tissue organization field theory (TOFT) of cancer premise that cells are not quiescent by default, but rather maintain continuous internal drive, while homeostasis is enforced on them by the tissue level of organization ( Sonnenschein and Soto, 2020 ). It is also consistent with the idea that aging affects the propensity for cancer development through the decrease in effective tissue homeostasis ( Capp and Thomas, 2021 ). Our conceptual framework may open the door to novel directions in cancer research and therapeutic development as it shifts the focus from looking for additional molecular targets to treating the learning cancer ecosystem as a whole ( Weinberg, 2014 ).…”
Section: Discussionsupporting
confidence: 90%
“…I read the manuscript entitled “Tissue‐disruption‐induced cellular stochasticity and epigenetic drift: Common origins of aging and cancer?” with great interest. [ 1 ] I agree with authors that tissue‐disruption‐induced cellular stochasticity associated with epigenetic drift is likely to be at the root of carcinogenesis.…”
supporting
confidence: 81%
“…However, it was recently shown that in breast tumors EMT is an inherent feature of most clones (which were found to harbor a major population of epithelial cells and a smaller and variable subpopulation of mesenchymal cells) [ 24 ], suggesting that the differentiation state of tumor cells is inherently unstable or plastic. Finally, since stochastic gene expression is normally controlled by cell-cell interactions [ 25 ], tissue disruption could produce a global destabilization of gene expression resulting in increased cellular stochasticity, and especially in high epigenetic and transcriptional diversity [ 26 , 27 , 28 ].…”
Section: The Origins Of the Increased Epigenetic And Transcriptional Heterogeneity In Cancermentioning
confidence: 99%